2013
DOI: 10.1097/opx.0b013e318282951b
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Multifocal and Monovision Contact Lens Correction

Abstract: Multifocal contact lens correction provided satisfactory levels of VA comparable with MV without compromising stereoacuity in this crossover study. The near vision significantly improved in the dominant eye, and the distance vision improved in the nondominant eye from 1 to 15 days with the MF lens, suggesting that patients adapted to the multifocality overtime, whereas this was not true for MV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
52
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 18 publications
13
52
1
Order By: Relevance
“…However, variability in stereopsis measurements for multifocal lenses has been previously reported (15,20,21) . In this study, HCVA at near distances that were recorded with all lenses were lower than pre viously reported values (15,(20)(21)(22)(23)(24)(25) , which is primarily attributable to the difference in methodology. Unlike other studies, we sought to measure the smallest paragraph that patients could "comfortably" read, which involved an additional subjective element in the objective resolution task.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…However, variability in stereopsis measurements for multifocal lenses has been previously reported (15,20,21) . In this study, HCVA at near distances that were recorded with all lenses were lower than pre viously reported values (15,(20)(21)(22)(23)(24)(25) , which is primarily attributable to the difference in methodology. Unlike other studies, we sought to measure the smallest paragraph that patients could "comfortably" read, which involved an additional subjective element in the objective resolution task.…”
Section: Discussioncontrasting
confidence: 70%
“…This study was limited by the small adaptation period. While this imitates what often occurs when patients first fit multifocal contact lenses in practice, changes in lens performance may occur over 4-15 days (9,22) . Longer term studies are required to determine if these study measures continue to predict performance over a longer period of time.…”
Section: Discussionmentioning
confidence: 92%
“…In terms of adaptation they found that subjective responses declined over the four days of contact lens wear. Fernandes et al also assessed adaptation of multifocal contact lenses and found that HCVA improved over 15 days of lens wear, though they did not assess changes in subjective vision responses [28]. The current study assessed visual performance within one hour of lens insertion.…”
Section: Multifocal Contact Lensesmentioning
confidence: 90%
“…The scientific literature shows good distance and near visual outcomes with simultaneous vision multifocal CLs [9][10][11][12][13][14][15][16][17][18]. However, some researchers have reported that prescribing rates of these CLs are low [19].…”
Section: Discussionmentioning
confidence: 99%